EFFECTIVENESS OF THE NUMBERED HEADS TOGETHER (NHT) MODEL BASED ON SNAKES AND LADDERS MEDIA ON STUDENTS' ENGAGEMENT IN SKI - Choirunisa Salsabila; Deden Makbuloh; Muhammad Mustofa (Jurnal Visipena, 2025)
Student engagement is a crucial indicator of successful educational outcomes. However, in practice, engagement levels often remain low, particularly in Islamic Cultural History (SKI) courses. Preliminary research conducted at MTs Negeri 2 Bandar Lampung revealed that only 2% of students actively engaged in asking questions to teachers or peers, indicating a predominantly passive attitude towards learning. This situation highlights the urgent need for innovative teaching methods that can effectively foster active student participation. Accordingly, this study empirically examines the effectiveness of the Numbered Heads Together (NHT) cooperative learning model, integrated with Snakes and Ladders game media, in enhancing students’ engagement in Islamic Cultural History (SKI). The research adopts a quantitative approach using a quasi-experimental design with a post-test-only control group framework. The sample consists of two intact groups from seventh-grade classes, selected via intact group sampling techniques. One class served as the experimental group, utilizing NHT with Snakes and Ladders media, while the other group was the control, applying the Jigsaw method. Data on learning activity were collected through questionnaires and analyzed using independent sample t- tests, along with effect size calculations. The findings revealed a significance level of 0.269 (> 0.05) and a Cohen’s d of 0.027, indicating no statistically significant difference between the experimental and control groups, with the treatment effect being negligibly small in practical terms. These results suggest that the effectiveness of the NHT model based on game media is context-dependent and influenced by students’ preparedness, self-confidence, and emotional factors. Consequently, for NHT to function optimally in enhancing student engagement, it requires strengthening of the affective domain alongside consistent reinforcement of cooperative learning practices.